STRENGTHENING EPP (ENGLISH PROFICIENCY PROGRAM) PROGRAM IN IMPROVING ENGLISH ABILITY OF MUHAMMADIYAH 2 TAMAN STUDENTS - Hidajati, Fitrijah; Jannah, Miftahol (State Institute of Islamic Studies (IAIN) Palu, 2019)
This paper discusses the importance of Strengthening the EPP (English Proficiency Program) Program in Improving Students' English Language Ability in Muhammadiyah 2 Middle School, Taman In this 21st century era, the literacy ability of students is closely related to the demands of reading skills that lead to the ability to understand information analytically, critically, and reflectively. The rapid development of technology has changed the landscape of education globally especially in facing the challenges of the industrial revolution 4.0 and preparing graduates (outputs) who will live in an era that will integrate technology thoroughly even blurring physical, digital and life boundaries biologically and is predicted to have a profound influence very big on the work environment, social and even culture that exists. This research is a qualitative-descriptive research which is expected to be able to uncover various information with a careful and meaningful description-analysis. Data sources in this study include the principal, vice principal of curriculum affairs, English language teacher. Data collection is done by interview, observation, and documentation. As for the data analysis technique through the stages of data reduction, data presentation and data analysis. The results of this research are (a) School based management program can be implemented by strengthening the EPP (English Proficiency Program) program (b) Strengthening the EPP (English Proficiency Program) program able to improve English language skills.